2020
DOI: 10.1080/01614940.2020.1823788
|View full text |Cite
|
Sign up to set email alerts
|

Halogenases for biosynthetic pathway engineering: Toward new routes to naturals and non-naturals

Abstract: Nature's repertoire of bio-halogenase enzymes is intriguing with halogenases from various natural product biosynthetic clusters that carry out site and region-specific halogenation of diverse bioactive precursors and molecules. Currently, we have a comprehensive catalogue of cryptic and non-cryptic halogenases that act on simple to complex aliphatic and aromatic molecular scaffolds. This will open up further synthetic and biosynthetic opportunities for C-H activation, ring formation and functionalization of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 248 publications
(279 reference statements)
0
21
0
Order By: Relevance
“…Flavin-dependent halogenase (Fl-Hal)-based selective activation of aromatic C–H positions has transformed integrated chemo–bio-synthesis in recent years. Fl-Hal enzymes PrnA, SttH, and PyrH for regiospecifically halogenated tryptophan 7, 6, and 5 positions, respectively, were studied extensively by different groups, providing an effective catalyst control for the followed Pd-based cross-coupling chemistries. As we identified that iaaM and iaaH enzymes could accept halogenated compounds at different positions, the possibility of utilizing Fl-Hals (PrnA, PyrH, and SttH) to install halogen bonds in tryptophan was explored. The halogenated tryptophan could be further processed via IAM pathway enzymes generating site-specific halogenated IAMs and IAAs.…”
Section: Resultsmentioning
confidence: 99%
“…Flavin-dependent halogenase (Fl-Hal)-based selective activation of aromatic C–H positions has transformed integrated chemo–bio-synthesis in recent years. Fl-Hal enzymes PrnA, SttH, and PyrH for regiospecifically halogenated tryptophan 7, 6, and 5 positions, respectively, were studied extensively by different groups, providing an effective catalyst control for the followed Pd-based cross-coupling chemistries. As we identified that iaaM and iaaH enzymes could accept halogenated compounds at different positions, the possibility of utilizing Fl-Hals (PrnA, PyrH, and SttH) to install halogen bonds in tryptophan was explored. The halogenated tryptophan could be further processed via IAM pathway enzymes generating site-specific halogenated IAMs and IAAs.…”
Section: Resultsmentioning
confidence: 99%
“…However, haloperoxidases, another group of peroxidases, mediate reactions of halide ions with hydrogen peroxide [ 100 ]. This class has identified three enzymes in mammals: lactoperoxidase, myeloperoxidase (MPO), and eosinophil peroxidase.…”
Section: Intracellular Sources Of Rosmentioning
confidence: 99%
“…Nowadays, computational methods are the easiest way to detect potential halogenating proteins for example using genome-mining tools like antiSMASH or Blastp [ 24 , 44 ]. These genome-mining methods are very useful for the detection of enzymes present in biosynthetic gene clusters (mainly for FDHs) [ 45 , 46 , 47 ].…”
Section: Halogenation Enzymesmentioning
confidence: 99%